Land-use choices: the case of conservation reserve program (CRP) re-enrollment in Kansas, USA. Issue 5 (2nd September 2016) - Caldas, Marcellus M.; Bergtold, Jason S.; Peterson, Jeffrey M.; Earnhart, Dietrich H.
ABSTRACT: Among the important alternatives for land conservation is the US Conservation Reserve Program (CRP) that celebrated its 30th anniversary in 2015. This paper explores how landowners decide on alternative land-use choices made available by the expiration of CRP contracts in Kansas. The study uses survey data and multinomial Logit models to predict land-use choices. Two models were tested. The first model does not incorporate variables concerning farmer perceptions and attitudes about land-use choices, while the second model does. The results show that CRP re-enrollment depends on factors, such as years of experience in cropping and percent of cropland irrigated. However, when perception variables are added, the models become more robust in explaining other land choice alternatives. The results suggest that as the perception of unfairness of more inflexible environmental policy rises, these farmers may be more likely to re-enroll their marginal land in the CRP program.